Intracerebroventricular streptozotocin induces impaired Barnes maze spatial memory and reduces astrocyte branching in the CA1 and CA3 hippocampal regions - Zappa Villar, María Florencia (2018)
Sporadic Alzheimer’s disease (SAD) is the most common form of dementia; therefore, there is an urgent need for a model that recapitulates the main pathologic hallmarks of this disease. The intracerebroventricular (icv) injection of streptozotocin (icv-STZ) in rats constitutes a promising model, and thus, icv-STZ rats develop insulin-resistant brain state and cognitive impairments. Even though a great piece of studies has hitherto described this system as a model for SAD, further behavioral and morphometric studies are still needed to fully characterize it. In this study, using Sprague Dawley rats, we evaluated short-term effects on behavior and hippocampus morphometry of the icv-STZ injection at two doses: 1 (STZ1) and 3 mg/kg (STZ3). We found that, following icv-STZ injection, STZ3 animals, but not STZ1, exhibited impairments in spatial reference learning and memory (Barnes maze test) and in recognition memory (object recognition test). Furthermore, the results from behavioral and morpho-histochemical data are compatible. STZ3 rats displayed Stratum Radiatum volume reduction and a decreased NeuN immunoreactivity (neuron loss) in hippocampal CA1 region, together with an increased immunoreactivity for microglial (Iba1) and astroglial (GFAP) markers (neuroinflammation). Sholl analysis revealed the vulnerability of hippocampal astrocytes to STZ in CA1 and CA3. Thus, both doses induced a reduction in process length and in the number of main processes, accompanied by a frank decrease in branching complexity. The present study provides important knowledge of this AD rat model. Overall, we found that the only high STZ dose induced severe and acute neurodegenerative lesions, associated with an inflammation process.